Effects of the Prolong Life With Nine Turn Method (Yan Nian Jiu Zhuan) Qigong on Brain Functional Changes in Patients With Chronic Fatigue Syndrome in Terms of Fatigue and Quality of Life - Xie, Fangfang; Guan, Chong; Gu, Yuanjia; You, Yanli; Yao, Fei (Frontiers in Neurology, 2022)
Background: Chronic fatigue syndrome (CFS) is characterized by persistent fatigue, which often leads to physical and psychological damage. The prolong life with nine turn method (PLWNT) Qigong is considered one of the complementary treatments for improving symptoms in patients with CFS. In this study, we used functional magnetic resonance imaging (fMRI) to study the effects of PLWNT intervention on the subjects with CFS. Methods: Thirty four CFS patients were randomly divided into PLWNT group and cognitive behavioral therapy (CBT) group. Both groups were taught by a highly qualified professor at the Shanghai University of Traditional Chinese Medicine once a week and were supervised online during the remaining 6 days at home, over 12 consecutive weeks. We calculated the regional rs-fMRI index amplitude of low-frequency fluctuations (ALFF) for all subjects. To study the changes of the brain network, we used the brain regions with significant differences in ALFF as the regions of interest for whole-brain functional connectivity (FC) analysis. The Multi-dimensional Fatigue Inventory 20 (MFI-20) and Short Form 36-item Health Survey (SF-36) were used for clinical symptom assessment to explore the possible correlation between the rs-fMRI indicators and clinical variations. Results: The ALFF values of the right superior frontal gyrus (SFG), and left median cingulate gyrus (DCG) were increased, whereas those of the left middle occipital gyrus (OG), right middle OG and left middle temporal gyrus (MTG) were decreased in PLWNT group. The FC values between the DCG and middle temporal gyrus (MTG), and those between the left OG and the right OG were enhanced. In addition, the SF-36 were positively with the left OG (r=0.524), SFG(r=0.517) and DCG(r=0.533), MFI-20 were negatively with the SFG(r=-0.542) and DCG(r=-0.578). These results were all corrected by FWE (voxel level p < 0.001, cluster level p < 0.05). Conclusion: CFS patients have abnormal regional spontaneous neuronal activity and abnormal functional connections between regions after PLWNT intervention. PLWNT can relieve the fatigue symptoms of CFS patients and improve their quality of life. The study was registered in the American Clinical Trial Registry (12/04/2018). Registration Number is NCT03496961.